Validação do subconjunto terminológico da CIPE para a pessoa idosa - Medeiros, Ana Claudia Torres de (2014)
Introduction: The increasing longevity leads health professionals, especially nurses, to worry about care for the elderly, especially in primary care. We seek to identify risk factors for promoting health and preventing diseases, thus providing a healthier aging. Objective: Validate the terminological subset of the International Classification for Nursing Practice (ICNP®) for the elderly. Method: Methodological study included the following stages: 1) mapping of the statements of diagnoses/nursing outcomes with previously agreed concepts of the ICNP® 2013; 2) preparation of operational definitions for the statements of diagnoses/nursing outcomes; 3) validation by expert consensus of operational definitions for the statements of diagnoses/nursing outcomes; 4) validation by consensus of nursing interventions for the statements of diagnoses/nursing outcomes validated in the previous stage; 5) reorganization of the subset according to the life model, with preparation of an instrument for elderly nursing consultation; and 6) clinical operationalization of the terminological subset of the ICNP® for the elderly. This study was approved by the Research Ethics Committee of the Center for Health Sciences of the Federal University of Paraiba (CCS/UFPB), under the Certificate of Presentation for Ethical Appreciation (CAAE) 24301613.9.0000.5188. Results and discussion: The cross-mapping resulted in 81 (63.8%) statements of diagnoses/nursing outcomes that were included and 46 (36.2%) that were not included in the ICNP® 2013. Operational definitions were prepared for the 127 statements included in the terminological subset of the ICNP® for the elderly, according to the factors that influence on the life activities of the life model, and 1 instrument for expert validation. There were 5 face to face meetings, totaling 11 hours of discussion, in June and July 2014, with approval by consensus of 105 (82.8%) diagnoses/nursing outcomes and their respective operational definitions; 4 diagnoses/nursing outcomes were classified into the environmental factor, 64 into the biological, 3 into the political and economic, 26 into the psychological, and 8 into the sociocultural. The validation by consensus of nursing interventions resulted in 101 statements of diagnoses/nursing outcomes, for which 441 nursing interventions were validated by consensus, totaling an average of 4.3 statements of nursing interventions per diagnosis for the elderly. There are 8 nursing interventions into the environmental factor, 281 into the biological, 8 into the political and economic, 107 into the psychological, and 37 into the sociocultural. The reorganization of the terminological subset of the ICNP® for the elderly was structured with: Guidelines for use; Importance to nursing; Theoretical model of the subset structure; Statements of the terminological subset; Instrument for elderly nursing consultation; and Example and case study. The clinical operationalization of the subset took place through 5 case studies, individually described and interpreted from a comprehensive viewpoint. Final remarks: We found out that it is possible to validate the terminological subset of the ICNP® for the elderly, since the statements of diagnoses/nursing outcomes are concepts included in the ICNP® 2013 and they show up as relevant for the nursing practice with the elderly.